HARMONIZATION OF WAHBAH ZUHAYLI’S PHILOSOPHY OF WASAṬ MEANING IN TAFSĪR AL-MUNĪR: SCHLEIERMACHER HERMENEUTICS ANALYSIS - Kustiadi, Umar (Sekolah Tinggi Agama Islam Sadra, 2024)
Every religious believer has various social interaction distortions. Likewise, the orientation that is presented experiences a distraction of thought from individuals toward the problem of religious understanding. In line with this, Islam comes with various faces according to the perspectives that some Muslims have claimed. Of course, this is the impact of misunderstandings related to religious understanding that is too fanatical and exclusive. This article will briefly discuss the alignment of the meaning of wasaṭ according to Wahbah Zuhaylī’s thoughts in his tafsir al-Munīr. This article aims to provide a new perspective on the meaning of wasaṭ with the perspective of grammatical and psychological hermeneutics carried out by Schleiermacher. The method used is descriptive analysis with Schleiermacher’s hermeneutic approach of looking for grammatical aspects and psychological aspects. As a result, the term wasaṭ finally reaches the limit of understanding interpretation and dispels the misunderstanding because the distance in tracing is quite comprehensive from the grammatical and psychological sides. At the same time, the harmonization of the meaning of wasaṭ is hermeneutically quite in line with the current conditions of modern society. Problematic issues that continue to grow do not mean that the solution and solution seekers stop but provide opportunities to bring up various solutions from the perspectives seen by the community.